2021
DOI: 10.2147/prom.s272075
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Validation of the EQ-5D-3L in Patients with Nontuberculous Mycobacterial (NTM) Lung Disease Caused by Mycobacterium avium Complex (MAC)

Abstract: Purpose This analysis evaluated the psychometric properties of the EQ-5D-3L among patients with Mycobacterium avium complex lung disease (MAC-LD). Methods Data from the Phase III CONVERT trial were analyzed. Study measures including the EQ-5D-3L, St. George’s Respiratory Questionnaire (SGRQ), the 6-minute walk test (6MWT), and percent predicted forced expiratory volume in 1 second (ppFEV 1 ) were collected at baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Both coefficients passed the threshold for tolerable reliability (Kappa range: 0.44–0.93; ICC: > 0.8). Our results replicate international findings, including those for rare diseases [ 39 , 42 ], suggesting that the EQ-5D-3L shows acceptable reproducibility in SCA (Supplementary Table 4 ). Nevertheless, the results must be interpreted with caution and be seen more as a tendency regarding the small sample size of stable patients ( N < 30).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Both coefficients passed the threshold for tolerable reliability (Kappa range: 0.44–0.93; ICC: > 0.8). Our results replicate international findings, including those for rare diseases [ 39 , 42 ], suggesting that the EQ-5D-3L shows acceptable reproducibility in SCA (Supplementary Table 4 ). Nevertheless, the results must be interpreted with caution and be seen more as a tendency regarding the small sample size of stable patients ( N < 30).…”
Section: Discussionsupporting
confidence: 88%
“…Several validation studies in different settings and patient populations found at least moderate associations between the EQ-5D and disease-specific instruments and clinical assessments [ 39 41 ]. Our study also confirmed moderate to strong correlations between EQ-5D-3L-dimensions, EQ-5D-3L index, and EQ-VAS with the disease-specific ratings of SARA, INAS, and ADL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation